Assessing the Legal and Institutional Challenges of Trademark Protection in Nigeria - Akuandna, Iliya Felix; David, Isaac; Ibrahim, Billison; Abubakar, Ahmed; Odekunle, Kehinde Adeleke; Challa, Lauretta Adeleke; Dalap, Gwam’aan Gillet; Oyebade, Hannah Eikojonwa (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The Nigerian government's goal for economic growth and increasing foreign investment has boosted commercial activity, necessitating the protection of Intellectual Property Rights (IPRs) in order to maintain a safe and competitive corporate environment. However, Nigeria continues to suffer from pervasive infringement, notably counterfeiting and piracy, which rob artists, producers, and inventors of the rewards of their labor and impede national progress. This research looks at the nature, historical evolution, and practice of intellectual property protection in Nigeria, with a particular emphasis on trademark enforcement. It examines the institutional architecture in charge of protecting IPRs and finds important difficulties such as ineffective laws, insufficient enforcement tools, limited institutional finance, and low public awareness. Despite the existence of legislative mechanisms aimed at reducing infractions, their impact is minor, emphasizing the need for stronger and more effective enforcement tactics consistent with worldwide best practices. Using a doctrinal research technique based on legislation, case law, and academic literature, the study examines the ramifications of ongoing IPR infringement as well as the limits of present regulatory procedures. The study indicates that a stronger intellectual property law in Nigeria is critical for increasing investor confidence, fostering local ingenuity, and promoting long-term economic growth.